Viewing as Text: Theorizing Visual Literacies in Introduction to Gender and Women’s Studies - Carrie Hart (Atlantis)
Abstract This paper examines the critical role that visual literacies often play in the introductory course to Gender and Women’s Studies. Drawing on transnational feminist scholarship, the author argues that theorizing visual literacies can provide a valuable entry point into considering the material and ideological stakes of feminist knowledge production.